Income diversification and household welfare in Uganda 1992-2012 - Rumman Khan; Oliver Morrissey (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2019)
We use six waves of national household surveys in Uganda, from 1992/3 to 2012/13, to study income diversification by households for a period of two decades during which the country saw sustained economic growth and poverty reduction. The income sources are agriculture (farming), agricultural wage, self-employment (informal), wage employment and remittances. We present estimates based on data from the individual surveys pooled and then, to capture dynamics and go some way towards addressing endogeneity, we provide estimates from a pseudo-panel. We find that households with more diversified income sources tend to lower consumption welfare, indicating diversification has mainly been due to push factors (the need for income pushing people into low earning activities). This is because much of the diversification has been into the agricultural wage sector, particularly amongst the poorest households who have also experienced reductions in remittances. Welfare (in terms of adult equivalent expenditure) is higher for households engaged in the non-agricultural wage sector, but growth in wage employment has been very low. This is one of the first studies to look at household welfare and income diversification at the national level (rural and urban) over such an extended period of time.
Keywords: I39; O12; O55; 330; Income diversification; Household welfare; Uganda